Spectrum and trigger identification of hemophagocytic lymphohistiocytosis in adults: A single-center analysis of 555 cases - Miao, Yi; Zhang, Jing; Chen, Qingqing; Xing, Lingxiao; Qiu, Tonglu; Zhu, Huayuan; Wang, Li; Fan, Lei; Xu, Wei; Li, Jianyong (Frontiers in Immunology, 2022)
Limited data are available about the underlying causes of hemophagocytic lymphohistiocytosis (HLH) in adults. We collected and analyzed the data of 555 cases of adult HLH. HLH in 242 patients were malignancies-related and lymphoid malignancies (42.0%, 233/555) were the most common causes. Aggressive natural killer-cell leukemia, diffuse large B-cell lymphoma, and extranodal natural killer/T-cell lymphoma, nasal type were the most common specified pathological subtypes. Epstein-Barr virus (EBV) (69.0%, 100/145) was the most common pathogen among the cases of infections-related HLH (26.1%, 145/555). Malignancies-related HLH showed male preponderance, more common splenomegaly, more severe anemia and thrombocytopenia, and significantly elevated soluble CD25. In patients with abnormal lymphoid cells in the bone marrow (BM) and increased EBV DNA copy number, 48.9% (45/92) of them were aggressive natural killer-cell leukemia. In patients with abnormal lymphoid cells in the BM and normal EBV DNA copy number, 66.2% (47/71) of them are B-cell non-Hodgkin lymphoma. In patients with elevated EBV DNA copy number but no abnormal lymphoid cells in the BM , 71.0% (98/138) of these cases were EBV infection. In conclusion, lymphoid malignancy is the most common underlying cause of adult HLH, followed by EBV infection. Based on the BM morphology and EBV load, we developed a diagnostic flow for rapid determination of the triggers for HLH.